If on-the-Job Trraining is So Important to Competitiveness, Why isn't There a Better Market for It - Aterido, Reyes (World Bank, Washington, DC, 2012)
There is no question that up-to-date job skills are critical to economic performance in today's rapidly changing and fiercely competitive global marketplace. Paradoxically, while the economic efficiency and innovation capacity offered by the upgrading of human capital is widely recognized, market forces have proven inadequate for stimulating and linking the demand and supply for this on-the-job training. In theory, employers, who seek a qualified workforce, would create a demand for training providers, who would compete with one another to offer relevant training. However, the demand for training suffers when there is lack of competitive pressure, low profitability, or market imperfections, which contribute to increased likelihood of mismatches between demand and supply. To remedy low levels of skills upgrading and market imperfections, partnerships between the public and private sectors in many industrial and developing countries alike have been formed to boost both competitiveness and employment. Yet these partnerships have often failed to adjust supply and demand of training. This note offers lessons from both the failures and successes of these partnerships in the interest of boosting economic growth through raising the training levels in the workplace.